When the game was war : the NBA's greatest season - Cohen, Rich (Random House, 2023)
"The 1980s were a transformative decade for the NBA. Since its founding in 1946, the league had evolved from a bruising, earthbound game of mostly nameless, underpaid players to one in which athletes became household names for their thrilling, physics-defying play. The 1987-88 season was the peak of that golden era, a year of incredible drama that featured a pantheon of superstars in their prime--the most future Hall of Famers competing at one time in any given season--battling for the title, and for their respective legacies. In When the Game Was War, bestselling author Rich Cohen tells the story of this incredible season through the four teams, and the four players, who dominated it: Larry Bird and the Boston Celtics, Magic Johnson and the Los Angeles Lakers, Isiah Thomas and the Detroit Pistons, and a young Michael Jordan and his Chicago Bulls. From rural Indiana to the South Side of Chicago, suburban North Carolina to rust-belt Michigan, Cohen explores the diverse journeys each of these iconic players took before arriving on the big stage. Drawing from dozens of interviews with NBA insiders, Cohen brings to vivid life some of the most colorful characters of the era--like Bill Laimbeer, Kareem Abdul-Jabbar, Danny Ainge, and Charles Oakley--who fought like hell to help these stars succeed. For anyone who longs to understand how the NBA came to be the cultural juggernaut it is today--and to relive the magic and turmoil of those pivotal years--When the Game Was War brilliantly recasts one unforgettable season and the four transcendent players who were at the center of it all"--